CD13/aminopeptidase N is a negative regulator of mast cell activation. Issue 6 (2nd March 2016) - Zotz, Julia S.; Wölbing, Florian; Lassnig, Caroline; Kauffmann, Marlies; Schulte, Uwe; Kolb, Andreas; Whitelaw, Bruce; Müller, Mathias; Biedermann, Tilo; Huber, Michael
ABSTRACT: Antigen‐induced mast cell (MC) activation via cross‐linking of IgE‐bound high‐affinity receptors for IgE (FcεRI) underlies type I allergy and anaphylactic shock. Comprehensive knowledge of FcεRI regulation is thus required. We have identified a functional interaction between FcεRI and CD13 in murine MCs. Antigen‐triggered activation of IgE‐loaded FcεRI results in cocapping and cointernalization of CD13 and equivalent internalization rates of up to 40%. Cointernalization is not unspecific, because ligand‐driven KIT internalization is not accompanied by CD13 internalization. Moreover, antibody‐mediated cross‐linking of CD13 causes IL‐6 production in an FcεRI‐dependent manner. These data are indicative of a functional interaction between FcεRI and CD13 on MCs. To determine the role of this interaction, CD13‐deficient bone marrow‐derived MCs (BMMCs) were analyzed. Intriguingly, antigen stimulation of CD13‐deficient BMMCs results in significantly increased degranulation and proinflammatory cytokine production compared to wild‐type cells. Furthermore, in a low‐dose model of passive systemic anaphylaxis, antigen‐dependent decrease in body temperature, reflecting the anaphylactic reaction, is substantially enhanced by the CD13 inhibitor bestatin (–5.9 ± 0.6°C) and by CD13 deficiency (–8.8 ± 0.6°C) in contrast to controls (–1.2 ± 1.97°C). Importantly, bestatin does not aggravate anaphylaxis in CD13‐deficient mice. Thus, we have identified CD13 as a novel negative regulator of MC activation in vitro and in vivo. —Zotz, J. S., Wölbing, F., Lassnig, C., Kauffmann, M., Schulte, U., Kolb, A., Whitelaw, B., Müller, M., Biedermann, T., Huber, M. CD13/aminopeptidase N is a negative regulator of mast cell activation. FASEB J. 30, 2225–2235 (2016). www.fasebj.org